Comparative assessment of vertical fracture resistance in endodontically treated roots with different obturating systems and techniques: a systematic review and network meta-analysis of in vitro studies - Guangxiao Li; Ying Li; Jingchen He; Shuyu Liu; Junshu Tang; Taiwei Jiao; Haiyan Sun (BMC, 2024)
Abstract Background This study conducted a thorough assessment of vertical root fracture (VRF) resistance of endodontically treated teeth filled with various canal-filling systems and techniques through frequentist network meta-analysis (NMA). Methods A systematic literature search was performed to retrieve relevant publications using PubMed, Embase, ScienceDirect, Web of Science, and Cochrane Library databases. The retrieval time range was from Jan 2000 to Sep 2023. The literature selection and data extraction were independently conducted by two investigators. Eligible studies were critically appraised for risk of bias and quality of evidence. Subsequently, we used the 'network' package in Stata/MP 17.0 software to compare the VRF resistance of roots treated with different obturating systems or techniques. Results Forty-eight trials involving 2724 single-canal roots were included in the NMA. The surface under the cumulative ranking curves indicated that Resilon/Epiphany (80.8%), although outdated, provided the highest VRF resistance among all obturating systems. This was followed by GP/iRootSP (55.5%), GP/MTA-Plus (47.9%), GP/AH-Plus (47.4%), GP/AH-26 (45.9%), and GP/ZOE (12.3%). The roots filled with Resilon/Epiphany showed better VRF resistance as compared to those filled with gutta-percha/AH-Plus (SMD = 0.77, 95%CI 0.10 to 1.45) and gutta-percha/zinc oxide eugenol (SMD = 1.64, 95%CI 0.47 to 2.80). The single cone technique (SCT) group displayed the highest VRF resistance, and roots filled with all techniques, except Thermafil, outperformed the positive control group. Conclusions Resilon/Epiphany demonstrated the greatest root strength among all six obturating systems, followed by GP/iRootSP and GP/MTA-Plus, which are calcium silicate-based systems. In contrast, the gutta-percha/zinc-oxide eugenol system exhibited the weakest performance. All canal-filling techniques, particularly the SCT, strengthen endodontically treated roots, except for the Thermafil technique. Further well-designed clinical trials with large sample sizes are essential for validation.